The effect of sewage sludge co-disposal and leachate recycling on refuse stabilization - Chapman, Grant Campbell (Department of Civil Engineering, 2023)
In the past sanitary landfill sites for solid waste disposal were regarded simply as containment sites so that the waste contents were isolated from the population. Various degrees of effort were made to reduce the impact of the waste in and around the site - in some cases none in other cases considerable but the prevailing attitude was that it was a disposal site - not a treatment site; consequently, the stabilization of waste in the site was largely disregarded and generally little effort was made to promote waste stabilization. Rapidly growing cities as a result of urbanization of the rural communities has placed management and operation of sanitary landfill sites under increasing pressure from two directions in that an increased metropolitan population not only produces more solid wastes but also makes the acquisition of appropriate landfill sites increasingly difficult and expensive. These problems are exacerbated by a heightened environmental awareness in large sectors of the public who are concerned that municipal wastes in general, but solids waste are properly managed so as to maximize safe disposal of the wastes and minimize the environmental impact of these operations. Such developments have considerably increased the responsibilities of the municipal engineers in waste treatment and disposal and has demanded alternative and innovative measures for these operations. As a result, sanitary landfills are becoming regarded as bioreactors in that much greater cognizance of the stabilization of the wastes in the landfill is being taken; also, greater efforts are being made to reduce the impact of the landfill on its surroundings by installing liners to reduce leachate contamination of surrounding groundwater and by burning methane gas to reduce air pollution.